Radiation grafting of fuctional polymers - Kathrina Nirmala, Manoharan (2013)
Non-migratory active food packaging has the potential to reduce the current food crisis which involves production, quality and safety aspects for consumption. Currently, the food industry is using added preservatives which possibly contain harmful ingredients that will enable food to last longer. Besides that, active packaging like cans or plastic contains wordings on the surface that can migrate into food product over a period of time hence it can be detrimental for the health of consumer. This work aims to prepare a film surface that will be used as packaging with non-migratory antimicrobial properties via gamma radiation grafting. Using a hydrophilic, biocompatible polymer polyethylene glycol diacrylate (PEGDA) as tether molecule. In this study, PEGDA was grafted onto the surface of polypropylene (PP) films which were irradiated using gamma ray with dosages ranging from 10kGy, 15kGy, 20kGy, 25kGy and 30kGy. The concentration for polymer solution is between 1% to 20%. In this study, N,N-dimethylaminoethyl methacrylate (DMAEMA) was used as an antimicrobial agent. It was later immobilized on the PP film surface which hve been grafted with PEGDA by covalent attachment. Grafting was done by dipping the irradiated films in the polymeric solution for two hours in water bath at 70oC while purging with nitrogen. The weight of the films before and after grafting were taken and calculated using degree of grafting. After that, the films were characterized by using attenuated total reflectance Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM) and tensile testing machine. The result showed that a high degree of grafting of more than 10% was achieved when the total radiation dose was lower than 50kGy and the concentration for monomer solution of PEGDA and DMAEMA is kept below 20% within optimum condition